2017
DOI: 10.1007/s10238-017-0458-1
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length in the gastric mucosa after Helicobacter pylori eradication and its potential role in the gastric carcinogenesis

Abstract: The molecular mechanisms of gastric carcinogenesis after Helicobacter pylori (H. pylori) eradication remain unclear. We examined the telomere length of gastric mucosa samples after successful H. pylori eradication in patients without and those with gastric cancer. Telomere length was measured by the real-time PCR among four different groups of biopsies: gastric body from subjects without history of H. pylori infection (Hp-: n = 23), gastric body from cancer-free subjects after H. pylori eradication (cancer-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…About 23 healthy participants without history of H. pylori infection were also enrolled who underwent upper gastroscopy for yearly checkup examination or for the complaints of abdominal discomfort (median age 53, female/male, 11/12). The study participants were partly recruited from our recent study investigating the histological gastritis, telomere length and gastric mucosal architecture in patients after successful H. pylori eradication . Fujita Health University of Medicine approved the protocol, and written informed consent was obtained from all participants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…About 23 healthy participants without history of H. pylori infection were also enrolled who underwent upper gastroscopy for yearly checkup examination or for the complaints of abdominal discomfort (median age 53, female/male, 11/12). The study participants were partly recruited from our recent study investigating the histological gastritis, telomere length and gastric mucosal architecture in patients after successful H. pylori eradication . Fujita Health University of Medicine approved the protocol, and written informed consent was obtained from all participants.…”
Section: Methodsmentioning
confidence: 99%
“…The study participants were partly recruited from our recent study investigating the histological gastritis, telomere length and gastric mucosal architecture in patients after successful H. pylori eradication. 7,14,15 Fujita Health University of Medicine approved the protocol, and written informed consent was obtained from all participants.…”
Section: Study Populationmentioning
confidence: 99%
“…Tahara et al. demonstrated that H. pylori ‐infected gastric cancer tissues and the adjacent noncancerous tissues possessed shorter telomere length than H. pylori ‐negative gastric tissues, and that the shortening of telomere length was associated with higher expression of IL‐1B and NF‐κB …”
Section: Deregulation Of Host Functionsmentioning
confidence: 99%
“…Telomere shortening in genomic DNA is an indirect footprint, which reflects an accumulation of oxidative stress and chromosomal instability as a result of lifelong infection. Tahara et al demonstratedthat H. pylori-infected gastric cancer tissues and the adjacent noncancerous tissues possessed shorter telomere length than H. pylorinegative gastric tissues, and that the shortening of telomere length was associated with higher expression of IL-1B and NF-κB 41.…”
mentioning
confidence: 99%
“…Tahara T demonstrated that telomere length in gastric cancer or adjacent noncancerous tissues with H. pylori infection was shorter than that in gastric tissues without H. pylori infection, and the shortened telomere was associated with upregulated expression of IL-1B and NF-κB. 7 Vacuolating cytotoxin antigen (VacA) is another important virulent factor of H. pylori, and almost all H. pylori strains carry the vacA gene, but only 50%-60% of strains express VacA, and different vacA genotypes have different virulence. In acidic environment, VacA can act on the Na + -K + ATPase of target cells and disrupt the ion-protein function, damage the lysosomes and endoplasmic reticulum, eventually resulting in cellular vacuolar degeneration.…”
Section: Introductionmentioning
confidence: 99%